Study of Menarche Experience on Students of FKM UMJ - Amira Mhuthia Adila; Munaya Fauziah; Bella Febriani; Deviana Aninda Putri; Dewi Risqan Marfiah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
According to the World Health Organization (WHO) about one-fifth of the world's population of adolescents aged 10-19 years. In Indonesia, 5.2% of women experience menarche under the age of 12 from 17 provinces. The purpose of this study was to find out in-depth the experience of menarche in adolescent girls, especially in the Muhammadiyah University of Jakarta. The type of research used is qualitative research. The statements of the four informants regarding their knowledge of menarche were good, with various attitudes, behaviors, and responses. Reproductive health education is needed at this menarche phase. FKM UMJ students have various experiences regarding menarche or their first menstrual period.